Efficiency of Breathing Exercises Used in Physical Therapy for 6-12-Year-Old Asthmatic Children's Respiratory Function - Vytautas Karuža; Eglė Lendraitienė (Lithuanian Sports University, 2018)
Background. The aim of the study was to assess the efficiency of breathing exercises for 6-12- year-old asthmatic children's respiratory function. Methods. The study involved 15 children, 9 boys (60%) and 6 girls (40%). The average age of all subjects was 9.07 ± 1.94 years. Boys' average age was 8.89 ± 1.90 years, and that of the girls - 8.33 ± 2.16 years. All subjects participated in physical therapy were breathing exercises were applied for four weeks, 30-45 minutes per day. Moreover, before and after treatment with breathing exercises they had Stange and Henci tests (samples of breathing); breathing muscle strength test with pneumotonometer and abdominal muscle endurance test. Results. After four weeks of physical therapy, the mean respiratory arrest inhalation statistically significantly increased by 11.16%, (p < .05). Exhaled breath with hold was 19.17% of the average change, but this change was not statistically significant (p > .05); inspiration pressure changed by 27.30% on average (p < .05); static abdominal muscle endurance significantly increased from 26.33 to 36.13%; right side muscle static endurance significantly increased by 31.78% and left side static muscle endurance changed by 19.43%. Conclusion. Breathing exercises applied for four weeks for children aged 6-12 years, suffering from bronchial asthma, are useful for increasing respiratory arrest aspiration, inspiration and expiratory pressure, and the abdomen, trunk muscle endurance, but they do not result in any changes in respiratory arrest exhaled. Keywords:  breathing exercises, physical therapy, bronchial asthma, respiratory function.